The Structure of the European Education Systems 2017/2018 : Schematic Diagrams. Eurydice Facts and Figures - (:unkn) unknown (My University, 2017)
"This report provides information on the structure of mainstream education in European countries from pre-primary to tertiary level for the 2017/18 school and academic year. It includes national schematic diagrams, an explanatory guide and a map showing the main organisational models of compulsory education. The information is available for 43 European education systems covering 38 countries participating in the EU's Erasmus+ programme." (editor; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 1.1 Allgemeinbildende Schule; I 2.2 Europa; Bildungssystem; Schulwesen; Europa